2022
DOI: 10.1155/2022/3565676
|View full text |Cite|
|
Sign up to set email alerts
|

High SIRPA Expression Predicts Poor Prognosis and Correlates with Immune Infiltrates in Patients with Esophageal Carcinoma

Abstract: Background. Signal regulatory protein alpha (SIRPA) is an inhibitory receptor expressed in macrophages and a potential therapeutic target in cancers. This study aims to investigate the functional role of SIRPA in esophageal carcinoma (ESCA). Methods. Based on the Oncomine and The Cancer Genome Atlas (TCGA) database, SIRPA expression and clinical value were determined. Gene set enrichment analysis (GSEA) was performed to predict the mechanism underlying the oncogene role of SIRPA. Spearman’s correlation analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…It should be mentioned that the prognostic significance of SIRPA expression is inconsistent across different cancer types. It has been reported that high SIRPA expression is a favorable factor in colorectal cancer [45], but it is associated with poor prognosis in diffuse large B-cell lymphoma, follicular lymphoma, non-small cell lung cancer, and esophageal carcinoma [46][47][48][49]. A plausible explanation for these opposing findings is that the M1/M2 TAM ratio and/or the tumor-phagocytotic capacity of TAMs in colorectal cancer would likely be higher than those of the second group of tumors where high SIRPA expression correlates with poor outcome.…”
Section: Prognostic Significance Of Cd47 and Sirpa Expression In High...mentioning
confidence: 99%
“…It should be mentioned that the prognostic significance of SIRPA expression is inconsistent across different cancer types. It has been reported that high SIRPA expression is a favorable factor in colorectal cancer [45], but it is associated with poor prognosis in diffuse large B-cell lymphoma, follicular lymphoma, non-small cell lung cancer, and esophageal carcinoma [46][47][48][49]. A plausible explanation for these opposing findings is that the M1/M2 TAM ratio and/or the tumor-phagocytotic capacity of TAMs in colorectal cancer would likely be higher than those of the second group of tumors where high SIRPA expression correlates with poor outcome.…”
Section: Prognostic Significance Of Cd47 and Sirpa Expression In High...mentioning
confidence: 99%
“…ThermControl v2.0.4, the melting temperature (TM) and aggregation (TAgg) temperature were determined. 20…”
Section: Stability Analysismentioning
confidence: 99%
“…Exploiting this physiological checkpoint, tumor cells often upregulate CD47 and thereby escape recognition and removal by macrophages (15,16). Similarly, enhanced expression of SIRPα by intratumoral monocytes/macrophages has recently been shown to be associated with poorer survival in 5 follicular lymphoma, colorectal cancer, intrahepatic cholangiocarcinoma, and esophageal cancer (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 97%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%